Bioinspired synthetic polymers-based inhibitors of Alzheimer's amyloid-β peptide aggregation. Issue 4 (5th January 2023) - Rupali,; Joseph, Blessy; Thomas, Sabu; Sen, Newton; Paschold, André; Binder, Wolfgang H.; Kumar, Sonu
Abstract : In this review, various types of synthetic polymer-based inhibitors of amyloid-β aggregations are discussed for their potential development as therapeutic agents for Alzheimer's disease treatment. Abstract : Alzheimer's disease (AD) is a progressive neurodegenerative disease with no current cure and limited treatment solutions, wherefore discovering of novel therapies remains a global challenge in biopharmaceutical industries. The pathological hallmark of AD is the fibrillogenesis of the amyloid-β (Aβ) peptide, and inhibition of Aβ aggregation is considered a primary and effective therapeutic approach to suppress AD progression. For combating this disease bioinspired synthetic macromolecules have been evoked as promising Aβ inhibitors, owing to their attractive and optimizable physico-chemical properties and ease of functionalization, in comparison to the other small-molecular analogues. This review article aims to summarize articles documenting synthetic polymer-based inhibitors of Aβ aggregations and highlight their potential as promising AD therapeutic agents. Furthermore, the chemical insights into the development of various classes of such polymeric inhibitors, and their modulatory effect on the molecular mechanisms of Aβ self-assembly are discussed here to promote advancement in amyloid-related drug discovery research.